Ekstrak Daun Rhizophora sp. Menghambat Pertumbuhan Bakteri Streptococcus agalactiae dan Edwarsiella tarda (RHIZOPHORA SP. LEAF EXTRACT INHIBITS THE GROWTH OF Streptococcus agalactiae AND Edwarsiella tarda) - Syawal, Henni; Karnila, Rahman; Dirta, Angraika; Kurniawan, Ronal (Jurnal Veteriner; Vol 18 No 4 (2017)DO - 10.19087/jveteriner.2017.18.4.604, 2018)
This study aimed to observe the inhibition capability of Rhizophora sp. leaf extract towards the Streptococcus agalactiae and Edwardsiella tarda bacteria. Rhizophora sp. leaf was extracted using ethanol. Inhibition action of Rhizophora sp. leaf extract towards Streptococcus agalactiae and Edwardsiella tarda was tested on TSA solid media. The concentration of Rhizophora sp. leaf extract used were 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000 ppm, and novobiocin antibiotic was used as a control. Each treatment was conducted three times. MIC (minimum inhibition concentration) was performed to determine the minimum dose that could inhibit the bacterial growth. The results showed that the inhibition value of Rhizophora sp. leaf extract at 2000 to 10000 ppm towards Streptococcus agalactiae was 8.60-16.30 mm, and 6.97-12.27 mm towards Edwardsiella tarda , whereas the inhibition value of novobiocin for both bacteria was 18.00-20.45 mm. The results of MIC value at dose of 2.000 ppm of Rhizophora sp. leaf extract was towards Streptococcus agalactiae with bacterial density of 165x108 CFU/mL, and towards Edwardsiella tarda 75x108 CFU/mL, respectively. In conclusion, Rhizophora sp. leaf extract had more bacteriostatic activity against Gram-positive bacteria ( Streptococcus agalactiae ) rather than the Gram-negative bacteria ( Edwardsiella tarda ).